2005
DOI: 10.1002/bip.20406
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stabilization of human albumin by medium‐ and short‐chain n‐alkyl fatty acid anions

Abstract: A comprehensive study of the thermal stabilization of defatted human albumin monomer by n-alkyl fatty acid anions (FAAs), formate through n-decanoate, was carried out by differential scanning calorimetry (DSC). The concentration of each ligand affording maximum thermal stabilization was determined; n-nonanoate provides the greatest stabilization but is only marginally better than n-octanoate and n-decanoate. The use of reversible thermodynamics and a two-state denaturation model for albumin has been validated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Ribonuclease has also been shown to bind two moles of chloride ion, resulting in significant structural stabilization (∼2-3 kJ/mol) (431). Stabilization of HSA has been observed from binding chloride (432) and carboxylates, such as formate and acetate (433).…”
Section: Anion Bindingmentioning
confidence: 96%
“…Ribonuclease has also been shown to bind two moles of chloride ion, resulting in significant structural stabilization (∼2-3 kJ/mol) (431). Stabilization of HSA has been observed from binding chloride (432) and carboxylates, such as formate and acetate (433).…”
Section: Anion Bindingmentioning
confidence: 96%
“…An average value of the primary transition from pooled plasma HSA samples (I–1, J, N, and O, all with fatty acids) gives a of T m1 = 68.2°C. Shrake et al also measured the T m1 and Δ H m of defatted HSA as 64.7°C and 242.9 kcal mol −1 , (1016 kJ mol −1 ) respectively …”
Section: Resultsmentioning
confidence: 99%
“…Previous DSC measurement by Shrake et al have demonstrated that the although HSA has a propensity to aggregate on denaturation, the unfolding transition itself is microscopically reversible with respect to the individual protein macromolecules . To analyze the DSC data, we used the Origin software package from the manufacturer to model the behavior of the heat capacity curves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleaning and stabilisation of HSA Albumin was prepared by the method of Chen (1967) and then stabilised by addition of octanoate according to Shrake et al (2005): a solution containing 50 mg/ml of human serum albumin in distilled water was prepared at room temperature. Then charcoal powder was added under continuous stirring (HSA:charcoal = 2:1 w/w) and the pH was adjusted to 3 with 1 M HCl.…”
Section: Preparation Of the Hsa-dtpa-gd Conjugatesmentioning
confidence: 99%